Hubungan Self Awareness dan Kematangan Karir Siswa SMK “X” Blitar - Fortuna, Nirma Dewi; Bisri, Mohammad; Priyambodo, Aji Bagus; Hapsari, Ayu Dyah (Flourishing Journal, 2022)
Abstract: The purpose of this study was to determine whether there is a relationship between self-awareness and career maturity of SMK "X" Blitar students. This study uses a quantitative research approach with a correlational research design. The population of this study was 137 students majoring in hospitality at SMK "X" Blitar with a sample of 102 students aged 15-20 years who were determined using accidental sampling technique. This study uses two instruments, namely the self-awareness scale and the career maturity scale. The self-awareness scale was adapted from Arabsharhangi & Noorozi (2014). The self-awareness scale consists of 39 items that are tested with the item discriminating power test with a correlation coefficient range of 0.30-0.819 and has a reliability of 0.923. The career maturity scale was constructed by researchers based on Donald E. Super's career maturity aspect. The maturity scale consists of 42 items that were tested with the item discriminating power test with a correlation coefficient range of 0.301-0.753 and has a reliability of 0.926. The results of data analysis show that the highest level of career maturity and self-awareness of students is in the high category. The hypothesis was tested using the Pearson's product moment technique and obtained a correlation coefficient of 0.465 with p = 0.000 (p 0.05). The test results show that there is a significant positive relationship between self-awareness and career maturity. These results indicate that the higher self-awareness, the higher the level of career maturity, where students are able to realize all the strengths, weaknesses, talents, interests and potentials that have an impact on students. Abstrak: Tujuan penelitian ini untuk mengetahui ada tidaknya hubungan self awareness dan kematangan karir siswa SMK “X” Blitar. Penelitian ini menggunakan pendekatan penelitian kuantitatif dengan desain penelitian korelasional. Populasi penelitian ini adalah 137 siswa jurusan perhotelan di SMK “X” Blitar dengan jumlah sampel 102 siswa berusia 15-20 tahun yang ditentukan menggunakan teknik accidental sampling. Penelitian ini menggunakan dua instrumen yaitu skala self awareness dan skala kematangan karir. Skala self awarness diadaptasi dari Arabsharhangi & Noorozi (2014). Skala self awareness terdiri dari 39 item yang diuji dengan uji daya beda item dengan rentang nilai koefisien korelasi item-total 0,30-0,819 dan memiliki reliabilitas 0,923. Skala kematangan karir dikonstruksikan peneliti berdasarkan aspek kematangan karir Donald E. Super. Skala kematangan karir terdiri dari 42 item yang diuji dengan uji daya beda item dengan rentang nilai koefisien korelasi item-total 0,301-0,753 dan memiliki reliabilitas 0.926. Hasil analisis data menunjukan bahwa tingkat kematangan karir dan self awareness siswa mayoritas berada pada kategori tinggi. Hipotesis diuji menggunakan teknik pearson’s product moment dan diperoleh koefisien korelasi sebesar 0,465 dengan p=0,000 (p ≤ 0,05). Hasil pengujian hipotesis menunjukkan bahwa terdapat hubungan positif yang signifikan antara self awareness dan kematangan karir. Hasil ini menunjukkan bahwa semakin tinggi tingkat self awareness maka semakin tinggi pula tingkat kematangan karir siswa, dimana siswa mampu menyadari segala kekuatan, kelemahan, bakat, minat dan potensi yang berdampak pada kematangan karirnya.